ECONIMIC EVALUATION OF POSSIBLE LEGALIZATION OF PROSTITUTION IN THE CZECH REPUBLIC - Kheil, Adam; Zajíček, Miroslav, 1975-; Vopravil, Jiří; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
Czech Republic same as many other countries has a national debt. Each state is looking for ways how to reduce their national debt and at best completely repay it. One of the potential sources of money for the state can be taxing the prostitution industry. Everybody knows what prostitution is but nobody can imagine how big the amount of money that revolves in this shadow market is and how many people work in this industry. This business is very well hidden especially to tax authorities in most countries and it is very sophisticated. Nobody neither politicians in the Czech Republic do not want to speak about this topic and try to find a common solution beneficial to all parties. This paper focuses more on prostitution in brothels and flats which sex workers renting for their work which specially in Prague and cities near to borders with Austria and Germany. During research I spoke with owners of the brothels and sex clubs in the Prague and their employees (sex workers) with porn actors who also have a lot of information and data on this topic. I also interviewed sex workers who have their own flats where they work which are still more frequently seen in the Czech Republic. I collected all data and estimated the value of the market with sex service in the Czech Republic and how big impact this shadow economy has on the GDP. I focus primary on Prague, the largest market for prostitutes in the country also due to the large number of tourists. Prostitution has tendency to decrease in most of the regions except of Prague. Also women who work as sex workers more years try to find ways how to tax their incomes to get pension in the future. Owners of the brothels would like to somehow also legalize system of prostitution because problems which they have with local authorities had rising tendency. Estimates show that each year prostitution business earn more than 8 billion Czech crowns which is 0.
% of GDP, but if we counted third parties the amount can be more than doubled.
Vedoucí práce: Miroslav Zajíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses